Teaching History of Bravery and the Politics of Textbooks in Nepal: A Critical Discourse Analysis - G.C., Saroj (SCHOLARS: Journal of Arts & Humanities, 2021)
This paper examines a saga of the brave history of Nepal which has often been part and parcel of school education in Nepal. The brave history in the textbooks has been treated as a means of enlightenment and a catalyst to cultivate national character. On close inspection, however, teaching history embarks a political enterprise – an articulation of interest to shape the idea of the citizenry. Using the method of critical discourse analysis and post-historicist ideas, this paper takes historical accounts attributed to three pillars of the national narrative of brave history – Bhimsen Thapa, Balbhadra Kunwar, and Prithvi Narayan Shah, as depicted in the government school textbooks for analysis. The paper examines how the history of bravery has been negotiated and maintained as a comfortable and simplistic narrative at the cost of teaching history more critically in order to inform students and examine emerging questions about the national heroes by excluding the other side of historical narratives. Finally, this paper proposes education at any level cannot be taken as value-neutral, and history should be studied historically.